The Strength of Several Types of Bamboo from Around Palu City as a Substitute for Wood in Construction - Erniwati; Ariyanti; Sahri Alam; Mutmainnah; Asniati; Rahmawati (Jurnal Penelitian Pendidikan IPA, 2025)
The use of bamboo as a substitute for wood for construction needs is increasing along with the decreasing availability of wood. Meanwhile, on the other hand the strength and durability of bamboo are different from wood, so it is necessary to conduct research to determine the strength of bamboo before it is used as a raw material for construction needs to replace wood. Based on this, this study aims to determine the types of bamboo found around Palu City and to test the strength of bamboo as a substitute for construction wood or other uses. This study was conducted in July–October 2025 at the Forestry Laboratory and Mechanical Engineering Laboratory of Tadulako University. The raw materials used in this study were types of bamboo that are widely found around Palu City aged 4–5 years. The tools used in this study were handsaws, calipers/vernier calipers, ovens, digital scales, and Universal Testing Machines (UTM) for testing the mechanical properties of bamboo. The results showed that the type of bamboo and the position of the base, middle, and tip affected the water content and density of the bamboo studied. The density value of bamboo showed a tendency from the base to the tip of bamboo; the value became higher. The flexural strength of bamboo batu is equivalent to wood of strength class IV, and the flexural strength of bamboo betung and bamboo tali is higher than the flexural strength of wood of the same strength class. The shear and tensile strength values of bamboo are not affected by the type and axial position. The tensile strength values of bamboo studied have met the allowable stress limit of bamboo for tensile stress.